Entwicklung und Probleme der Agrarreform in Algerien - Trautmann, Wolfgang (ERDKUNDE, 1979)
This paper is mainly concerned with the aims, effects and problems of the Algerian agrarian reform, which took place in several stages after 1962. Following the setting up and reorganisation of the socialist sector, including the self governing estates and the co-operatives of war veterans on formerly French settlers' land, a phased agrarian revolution was begun, which tackled the division and distribution of agriculturally utilisable public land, the dispossession of large-scale native landowners and the restructuring of the steppe areas. This was accompanied by the setting up of state-directed co-operatives, which establish the central significance of the communal multi-purpose co-operatives for services, and by the founding of so-called socialist villages, which were chiefly intended for the provision of accommodation for the recipients of farm land. The main problems of the present development include the lack of land reserves, deficits in the balances of most land use collectives, little differentiation in the economic structure as well as the unattractiveness of the new institutions.